Finance for on-farm investments in dairy production in Kenya - Wilkes, Andreas; Dijk, Suzanne van; Odhong’, Charles (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
About 2 million rural households in Kenya produce milk. With about 1800 liters per cow and year, average annual milk production per cow on smallholder dairy farms is low. As a result, production costs per kilogram of milk are high, and profit margins for many farmers are slim. Low cow productivity is also associated with high greenhouse gas (GHG) emission intensity. In 2010, Kenya’s livestock emitted about 16.6 million tonnes of carbon dioxide equivalents (CO2e), of which about 20% was from dairy cattle.